PERAN PENDIDIKAN AGAMA KRISTEN MEMBENTUK INDIVIDU YANG MODERAT DALAM KEBERAGAMAN - Deni Yanto Birrang Allo; Mardika Gusmino; Sumiaty Sumiaty (Masokan Ilmu Sosial dan Pendidikan, 2023)
This article aims to examine religious moderation in Indonesia from the perspective of Christian Religious Education. Indonesia, which is known for its diversity in terms of culture, ethnicity, language, and even religion, is certainly one of the riches that Indonesia itself has. This is what makes Indonesia known for its diversity. Looking at the vastness of Indonesia, of course, brings up the big question: Can diversity in Indonesia work well and not cause chaos? Moreover, from a religious perspective, it is certainly not easy to achieve a society that can respect each other in terms of daily actions and behavior between people of different religions. The type of research used is literature study (library research). The type of research used is qualitative research with a literature study method (library research) regarding Christian Religious Education, which encourages a moderate attitude in dealing with diversity. The literature study method is a series of activities related to collecting library data, reading and taking notes, and managing research materials. Data was obtained by tracing several research results related to moderation in religion based on facts that have occurred in Indonesia and Christian Religious Education. Data was collected and then analyzed using Huberman's theory. The research results show that Christian Religious Education has a very important role in instilling Christian values in every individual by imitating Christ as the main figure in Christianity. By living these Christian values, individuals will be able to apply love to others, respect differences, be able to communicate well, and develop services to the community and other humanitarian actions without looking at differences. Artikel ini bertujuan untuk mengkaji moderasi beragama di Indonesia dari segi Pendidikan Agama Kristen. Indonesia yang dikenal akan berbagai keberagaman baik dari segi budaya, suku, bahasa, bahkan agama tentunya menjadi salah satu kekayaan yang dimiliki oleh Indonesia sendiri. Melihat Indonesia yang sangat luas, tentunya membawa pertanyaan besar bahwa: Apakah keberagaman di Indonesia ini bisa berjalan dengan baik dan tidak menimbulkan kekacauan? apalagi ditinjau dari segi agama tentunya bukan hal yang mudah dalam mencapai masyarakat yang bisa saling menghargai baik dari segi tindakan dan perilakunya sehari-hari antar umat yang beragama.  Jenis penelitian yang digunakan adalah studi literatur (library research).  Jenis penelitian yang digunakan adalah penelitian kualitatif dengan metode studi literatur (library research) yakni mengenai Pendidikan Agama Kristen yang mendorong sikap moderat dalam menghadapi keberagaman. Data diperoleh melalui penelusuran beberapa hasil penelitian yang terkait moderasi dalam beragama berdasarkan fakta-fakta yang telah terjadi di Indonesia. Data yang telah dikumpulkan kemudian dianalisis dengan mengacu pada teori Huberman. Hasil penelitian menunjukkan bahwa Pendidikan Agama Kristen memiliki peran yang sangat penting dalam menanamkan nilai-nilai kekristenan pada setiap individu dengan meneladani Kristus sebagai tokoh utama dalam kekristenan. Dengan menghidupi nilai-nilai kekristenan tersebut individu akan bisa menerapkan kasih kepada sesama, menghargai perbedaan, mampu berkomunikasi dengan baik, serta mengembangkan pelayanan pada masyarakat dan aksi-aksi kemanusiaan lainnya tanpa melihat perbedaan.